Implementation of Marketing Strategic Base On Artificial Intelligence (Ai) In The Islamic Paradigm On Alfi Huraiyah Hijab - Rahmi Suaida, Nur Aisyah; Abidin, Mohammad Zaenal (University of Darussalam Gontor, 2024)
Artificial Intelligence (AI) based marketing has become an important innovation in modern business strategies. This study aims to examine the implementation of AIbased marketing strategies within the Islamic paradigm at Alfi Huraiyah Hijab. The methodology used is qualitative research with data collection techniques through observation, interviews, and documentation. The research findings indicate that Alfi Huraiyah Hijab has applied AI-based marketing strategies in several aspects, such as the use of chatbots to interact with customers, data analysis to understand consumer preferences, and optimization of promotions through digital platforms. This AI implementation helps improve operational efficiency, speed up responses to customer demands, and strengthen consumer engagement. However, the application of this technology is still limited to certain functions and has not yet been fully integrated into the entire business process. From an Islamic perspective, the marketing strategies applied at Alfi Huraiyah Hijab also consider sharia principles such as honesty, responsibility, and fairness, while avoiding elements of gharar and tadlis that could harm any party. In conclusion, the application of AI in marketing strategies not only benefits the company in enhancing competitiveness and performance but can also be aligned with Islamic ethical values to create more sustainable business practices. Keywords: Marketing strategy, Artificial Intelligence, Chatbot, Islamic paradigm, Alfi Huraiyah Hijab.